2018
DOI: 10.1071/an16437
|View full text |Cite
|
Sign up to set email alerts
|

Endoparasite and nutritional status of Suffolk lambs in seven production systems

Abstract: Lambs are the most susceptible category for parasite infections; therefore, the choice of the production system can influence nutritional status and reduce parasite infections. The present study aimed to evaluate the endoparasites and nutritional status of meat lambs in seven production systems. In the feedlot, they were (S1) early weaned lambs in feedlot and (S2) unweaned lambs in feedlot with controlled suckling. On pasture, they were (S3) early weaned lambs on pasture without supplementation, (S4) early wea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 38 publications
1
10
0
1
Order By: Relevance
“…In this last group, three lambs performed well without the need for anthelmintic treatment. Despite the individual variation, it was possible to observe that in general, the well-nourished animals presented higher capacity to withstand the deleterious effects of parasitism, in agreement with other studies (CARVALHO et al, 2015;KHAN et al, 2017;SALGADO et al, 2017). It is necessary also to emphasize that because lambs under the basal diet received only a small quantity of concentrate, they grazed on average 1.7 hours more than the supplemented lambs.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In this last group, three lambs performed well without the need for anthelmintic treatment. Despite the individual variation, it was possible to observe that in general, the well-nourished animals presented higher capacity to withstand the deleterious effects of parasitism, in agreement with other studies (CARVALHO et al, 2015;KHAN et al, 2017;SALGADO et al, 2017). It is necessary also to emphasize that because lambs under the basal diet received only a small quantity of concentrate, they grazed on average 1.7 hours more than the supplemented lambs.…”
Section: Discussionsupporting
confidence: 88%
“…( SCHOEMAN, 2000). Similarly, improvement in the productive performance and reduction in the degree of infection have been reported in lambs of other breeds supplemented with concentrate in other regions of Brazil (TONTINI et al, 2015;MELO et al, 2017;SALGADO et al, 2017). Precautionary treatment given to lambs with PCV values lower than 23% was an approach similar to that recommended to prevent haemonchosis in the FAMACHA  method, in which the clinical category 3 corresponds to PCV = 18% to 22%.…”
Section: Discussionmentioning
confidence: 78%
“…The implications of production systems on performance, meat quality and economical aspects have been investigated by different researchers (Macedo et al, 2000a;Poli et al, 2008;Salgado et al, 2018), but it is still a point of discussion among scientists, producers and the meat industry. In this way, the objective of this study was to compare the influence of different lamb finishing systems on performance, as well as carcass and meat quality.…”
Section: Introductionmentioning
confidence: 99%
“…This recommendation aimed to ensure the best performance of animals even under different endoparasite challenge. The production systems can influence parasitic infection in lambs, such as weaning of lambs or feed supplementation, and can be relevant to the response to parasites (Salgado et al, 2018). Depner et al (2007) reported no significant effect of FMC and prophylactic strategies on performance of Ile de France lambs between four and eight months old in Rio Grande do Sul, Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…Pasture-based sheep production is more challenging to young animals due to their high susceptibility to parasite infections , since nutritional management and parasite control are crucial for , Alda Lúcia Gomes Monteiro 5* their performance (Salgado et al, 2018). The immunity against parasites increases at different levels with age (McRae et al, 2015), and the strategy for parasite control must contribute to achieving the maximum productivity of animals under parasite challenge.…”
Section: Introductionmentioning
confidence: 99%